1988
DOI: 10.1161/01.hyp.11.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Formation of angiotensin II by tonin-inhibitor complex.

Abstract: SUMMARY Enzymatic activity of tonin-o^-macroglobulin complex was studied in vitro and in vivo, using an immunoimmobilization technique. Tonin-ai-macroglobulin complex, which was immunologically immobilized by anti-a r macroglobulin antibody covalently coupled to agarose gels, could quantitatively hydrolyze angiotensin I and synthetic tridecapeptide renin substrate to form angiotensin II. However, the solid-phase antibody-bound tonin-a,-macroglobulin complex could not hydrolyze the plasma protein renin substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Cathepsin G and chymase can convert angiotensin I to angiotensin II [34, 35, 36, 37, 38, 39, 40, 41]. Converting enzyme inhibitors do not inhibit these enzymes.…”
Section: Proximal Tubule Renin-angiotensin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsin G and chymase can convert angiotensin I to angiotensin II [34, 35, 36, 37, 38, 39, 40, 41]. Converting enzyme inhibitors do not inhibit these enzymes.…”
Section: Proximal Tubule Renin-angiotensin Systemmentioning
confidence: 99%
“…Converting enzyme inhibitors do not inhibit these enzymes. In addition, other proteases such as kallikrein and tonin can generate angiotensin II directly from angiotensinogen [39, 40, 41]. Yosipiv and El-Dahr [38]showed that angiotensin II was generated in the newborn rat kidney in the presence of a converting enzyme inhibitor, indicating the presence of alternate modes of angiotensin II production.…”
Section: Proximal Tubule Renin-angiotensin Systemmentioning
confidence: 99%
“…32,33 Tonin is normally inactivated in plasma by the endogenous inhibitor alpha 1 -macroglobulin, however, it has recently been shown that even when bound to alpha 1 -macroglobulin, tonin can still generate angiotensin II, which is resistant to ACE inhibition. 34 …”
Section: Alternative Angiotensin II Generating Enzymesmentioning
confidence: 99%
“…[27][28][29][30] Recently, an aspartyl protease with cathepsin D-like properties was shown to convert Ao to Ang I in adult rat myofibroblasts isolated from ventricular scar tissue. 31 This suggests that unlike resident cardiac fibroblasts, 1,5,7 these transformed fibroblastlike cells synthesize Ang I via a non-renin-dependent pathway.…”
Section: Nonclassical Ras Componentsmentioning
confidence: 99%